Norovírus Associated Encephalopathy - Salva, I (2011)
clinical presentation is self limited. It is classified into five groups (genogroups I through V). There are numerous reports of neurologic complications, namely afebrile seizures, but only two reports of associated encephalopathy. Case Report: A 12 month old girl with previous history of a pneumonia treated with amoxicillin-clavulanic acid and clarythromycin, presented in our emergency department with strabismus, ataxia for 3 days, later associated with vomiting and diarrhea. On admission she had ataxia and an episode of strabismus, but her later neurologic exam was normal. Laboratory data revealed: 10,9 g/dL hemoglobin, 11.200/μL leukocytes, 29,1% neutrophils and 65,2% lymphocytes, 488.000/μL platelets and negative CRP. The brain MRI showed middle ear, maxillary sinus and ethmoidal opacification, with no other abnormalities. During the first day of admission she had a tonic (?) seizure for 20 minutes. CSF analysis showed 5,6 cells/μL, 100% lymphocytes, 80 mg/dL glucose and 154,1 mg/dL protein. The EEG revealed short duration paroxystic activity located to the vertex. She was treated with acyclovir, ciprofloxacin, cefthriaxone and phenytoin. Her symptoms resolved by the third day of admission. Blood samples were tested for numerous pathogens, including serology for Borrelia, which was positive for IgG but negative for IgM. Fecal sample analysis revealed positive PCR for norovirus, although it was negative in CSF samples. IL-6 was measured in the CSF and was negative (5,8 pg/mL). She had a history of recurrent otitis media and pernieal candidiasis, which led to a detailed immune function study, which showed Immunology tests revealed diminished IgA (< 0,244 g/L) and absent antibody response to vaccinations. Since she was only 13 months old when she was tested, only follow up will determine the relevance of these values. Follow up at two years of age showed no delays and a normal development. Conclusion: Norovirus encephalitis is a rare entity, although gastrointestinal infection with this agent is relatively common. Here we present a case of a probable norovirus associated encephalopathy, although PCR for norovirus was negative in CSF samples and there was no CSF cytokine increase. It was not associated with adverse neurologic outcome and so far her development is normal, unlike the evolution described in previous case reports.